Detection of «problem» areas in the power supply circuit for verification of calculated electrobalances - Находов, Володимир Федорович; Бориченко, Олена Володимирівна; Іванько, Дмитро Олегович; Якобюк, Ірина Вікторівна (Eastern-European Journal of Enterprise Technologies, 2015)
The paper deals with the issue of identifying the areas in the power supply circuit and types of equipment that create the greatest uncertainty in constructing the electrical balances of an industrial facility. For this purpose, a probabilistic-statistical method and expert survey are used. Expert surveys were conducted for more information about power consumption. This allows to define an interval of electric energy consumption of each type of equipment. Identifying not only the intervals of consumption, but also the frequency was proposed. Determining the most “problem” areas for monitoring energy efficiency at industrial enterprises allows the verification of electrical balances obtained by computational-analytical or probabilisticstatistical methods. Through a series of calculations, the areas, which make the largest uncertainty and require installing additional metering devices were defined. These calculations are needed to develop an operational control system of energy efficiency.